Meningkatkan Kemampuan Literasi Anak melalui Metode Small Step System di biMBA AIUEO Griya Satria Mandalatama - Damiri, Adam; Astriyanti, Riska; Difana, Nailan Reski (J-PGMI: Jurnal Pendidikan Guru MI, 2024)
This research aims to analyze the effectiveness of the Small Step System method in improving the literacy skills of early childhood children at biMBA AIUEO Griya Satria Mandalatama. The research method used is qualitative with a case study research design. Data was collected through observation, interviews, and documentation. The results of the research show that the Small Step System method is proven to be effective in improving the literacy skills of early childhood children at biMBA AIUEO Griya Satria Mandalatama. This is evidenced by the increased ability of children in reading, writing, and understanding the content of the reading.